2008
DOI: 10.15232/s1080-7446(15)30886-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corn Processing in Finishing Diets Containing Wet Distillers Grains on Feedlot Performance and Carcass Characteristics of Finishing Steers

Abstract: An experiment evaluated the effects of six corn processing methods in feedlot diets containing 30% (DM basis) wet distillers grains plus solubles (WDGS). Treatments consisted of whole corn, dry-rolled corn, a dry-rolled/ high-moisture corn mix, high-moisture corn, steam flaked corn, and fine ground corn. The ADG was highest for steers receiving dry-rolled corn, high-moisture corn, or a 50:50 blend of dry-rolled and high-moisture corn. Feed conversion was best for steers receiving high-moisture corn. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…However, Vander Pol et al (2006a) found similar G:F for SFC-and DRC- fed cattle when 30% WDGS was included in the diet, and ADG was significantly decreased for cattle fed SFC compared with DRC or HMC. Drouillard et al (2005) also obtained less response to the combination of WDGS and SFC than expected and suggested the optimal level of WDGS was less than the 30% level used by Vander Pol et al (2006a). Corrigan et al (2007) evaluated the interaction between WDGS inclusion and grain processing method.…”
Section: Grain Processingmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Vander Pol et al (2006a) found similar G:F for SFC-and DRC- fed cattle when 30% WDGS was included in the diet, and ADG was significantly decreased for cattle fed SFC compared with DRC or HMC. Drouillard et al (2005) also obtained less response to the combination of WDGS and SFC than expected and suggested the optimal level of WDGS was less than the 30% level used by Vander Pol et al (2006a). Corrigan et al (2007) evaluated the interaction between WDGS inclusion and grain processing method.…”
Section: Grain Processingmentioning
confidence: 97%
“…Vander Pol et al (2006a) fed DRC, SFC, and HMC with 30% WDGS to finishing cattle. From the metaanalysis, this 30% inclusion level with DRC or HMC would be optimal for rate and efficiency of gain.…”
Section: Grain Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first factor was corn processing method (DRC, HMC, or SFC), and the second factor was WDGS dietary inclusion level (0,15,27.5,and 40%;DM basis). The greatest level of WDGS was chosen because Vander Pol et al (2008) reported that optimal G:F in finishing steers was achieved with 40% WDGS (DM basis) in diets based on a 1:1 ratio of HMC and DRC. Upon arrival at the feedlot, steers were individually identified, vaccinated with Bovi-Shield Gold 5 and Somubac (Pfizer Animal Health, New York, NY), and injected with Dectomax Injectable (Pfizer Animal Health).…”
Section: Expmentioning
confidence: 99%
“…Vander Pol et al (2008) reported that, in diets containing 30% corn WDGS, steers fed a diet based on HMC and DRC had ADG that were greater and G:F that were equal or greater than steers fed a diet based on SFC. In diets containing no WDGS, G:F was greater in SFC-based diets compared with diets based on HMC and DRC (Huck et al, 1998;Cooper et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%